NORTHEAST ASIA AND SOUTHEAST ASIA: THE GEOPOLITICAL NEXUS IN INDO-PACIFIC SECURITY - Nathan, K.S. (AEI Insights, 2025)
This article focuses on the strategic (economic, political and security) linkages that govern interactions between the major and regional powers in the Indo-Pacific region. It argues that the principal drives of Indo-Pacific security are the strategic significance of the region in terms of its geopolitical location, its economic and demographic characteristic which attract the attention and engagement of the primary and secondary actors involved, and the conflict and cooperation scenarios that link Northeast Asia and Southeast Asia. The paper also argues that that a key and inevitable component of Indo-Pacific security is the strategic role of the United States, its relations with all key actors of the Indo-Pacific region and its overwhelming military presence and projection capabilities that cannot be ignored by all actors especially rising China and its perceived threats to U.S. regional and global interests. The paper concludes that despite the existing superpower tensions and rivalries, there is a role for deterrence and balance of power strategies to mitigate existing territorial and resource competitions as in the South China Sea, with ASEAN playing a moderating and interlocutory role in the effort to maintain regional order and stability, thus directly and indirectly impacting Indo-Pacific security.